Association of the Salivary Microbiome With Animal Contact During Early Life and Stress-Induced Immune Activation in Healthy Participants - Langgartner, Dominik; Zambrano, Cristian A.; Heinze, Jared D.; Stamper, Christopher E.; Böbel, Till S.; Hackl, Sascha B.; Jarczok, Marc N.; Rohleder, Nicolas; Rook, Graham A.; Gündel, Harald; Waller, Christiane; Lowry, Christopher A.; et al. (Frontiers in Psychiatry, 2020)
The prevalence of stress-associated somatic and psychiatric disorders is increased in environments offering a narrow relative to a wide range of microbial exposure. Moreover, different animal and human studies suggest that an overreactive immune system not only accompanies stress-associated disorders but might even be causally involved in their pathogenesis. In support of this hypothesis, we recently showed that urban upbringing in the absence of daily contact with pets, compared to rural upbringing in the presence of daily contact with farm animals, is associated with a more pronounced immune activation following acute psychosocial stressor exposure induced by the Trier Social Stress Test (TSST). Here we employed 16S rRNA gene sequencing to test whether this difference in TSST-induced immune activation between urban upbringing in the absence of daily contact with pets (n = 20) compared with rural upbringing in the presence of daily contact with farm animals (n = 20) is associated with differences in the composition of the salivary microbiome. Although we did not detect any differences in alpha or beta diversity measures of the salivary microbiome between the two experimental groups, statistical analysis revealed that the salivary microbial beta diversity was significantly higher in participants with absolutely no animal contact (n = 5, urban participants) until the age of 15 compared to all other participants (n = 35) reporting either daily contact with farm animals (n = 20, rural participants) or occasional pet contact (n = 15, urban participants). Interestingly, when comparing these urban participants with absolutely no pet contact to the remaining urban participants with occasional pet contact, the former also displayed a significantly higher immune, but not hypothalamic-pituitary-adrenal (HPA) axis or sympathetic nervous system (SNS) activation, following TSST exposure. In summary, we conclude that only urban upbringing with absolutely no animal contact had long-lasting effects on the composition of the salivary microbiome and potentiates the negative consequences of urban upbringing on stress-induced immune activation.